Temperature-Dependent Long-term and Short-term Stability of Human Epidermal Growth Factor Receptor 2 Antigenicity on Pathology Slides - Liam Scott; Julia Benanto; Charles J. Robbins; Katherine Bates; Mengni He; Nay Nwe Nyein Chan; David L. Rimm (Archives of Pathology & Laboratory Medicine, 2026)
Context.— Immunohistochemistry-based assessment of human epidermal growth factor receptor 2 (HER2) is increasingly useful for clinical decision-making in breast, gastroesophageal, and other cancers. Retroactive use of cancer tissue for research purposes is increasing alongside increased understanding of HER2’s role in determining cancer outcomes. Best practices for formalin-fixed, paraffin-embedded (FFPE) tissue handling are addressed in guidelines for diagnostic and scientific activities; however, preanalytic variables arising after tissue embedding and sectioning are minimally discussed. Objective.— To quantify the loss of HER2 antigenicity that occurs on sectioned FFPE slides over long- and short-term timescales, in both room-temperature and freezer conditions. Design.— Surplus FFPE microarray slides from years-prior experiments, stored either at room temperature or in a −80°C freezer, were paired with block-matched, freshly cut slides for analysis of postsectioning epitope degradation. To evaluate short-term changes in epitope availability, a set of FFPE slides was serially stained by immunofluorescence during a 2-month period, using standardization to mass spectrometry values to enable standardized quantification of antigen in amol (attomoles)/mm 2 . Results.— Significant degradation of HER2 antigen on FFPE slides occurs over a period of years when slides are stored at room temperature, but not when stored at −80°C. In either condition, the amount of degradation that occurs within a 2-month timescale is negligible compared to variation attributable to tumor heterogeneity and interrun variability. Conclusions.— Room-temperature storage of FFPE slides appears to be safe for HER2 measurement when staining will occur within 2 months. The “shelf life” of slides stored at −80°C is at least 1 year.